2018
DOI: 10.1002/jcph.1069
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Individual Serum Infliximab Concentrations in Inflammatory Bowel Disease by a Bayesian Dashboard System

Abstract: Despite a robust exposure-response relationship of infliximab in inflammatory bowel disease (IBD), attempts to adjust dosing to individually predicted serum concentrations of infliximab (SICs) are lacking. Compared with labor-intensive conventional software for pharmacokinetic (PK) modeling (eg, NONMEM) dashboards are easy-to-use programs incorporating complex Bayesian statistics to determine individual pharmacokinetics. We evaluated various infliximab detection assays and the number of samples needed to preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 39 publications
(54 reference statements)
2
32
0
Order By: Relevance
“…[4][5][6] Broadly speaking, TDM strategies advocate populationbased target trough concentrations for dose adjustment, using a reactive rather than proactive approach. [7][8][9] Integration of pharmacodynamic (PD) outcomes to yield PK/PD models is rare, but these could feasibly be included in Bayesian prediction algorithms to predict and adjust dosing strategy on an individual level. 10,11 To date, investigation of the effectiveness and utility of TDM has largely been confined to tumor necrosis factor inhibitors, the first of many cytokine-targeted biologic therapies in immune-mediated inflammatory diseases.…”
Section: Study Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Broadly speaking, TDM strategies advocate populationbased target trough concentrations for dose adjustment, using a reactive rather than proactive approach. [7][8][9] Integration of pharmacodynamic (PD) outcomes to yield PK/PD models is rare, but these could feasibly be included in Bayesian prediction algorithms to predict and adjust dosing strategy on an individual level. 10,11 To date, investigation of the effectiveness and utility of TDM has largely been confined to tumor necrosis factor inhibitors, the first of many cytokine-targeted biologic therapies in immune-mediated inflammatory diseases.…”
Section: Study Highlightsmentioning
confidence: 99%
“…Broadly speaking, TDM strategies advocate population‐based target trough concentrations for dose adjustment, using a reactive rather than proactive approach . Integration of pharmacodynamic (PD) outcomes to yield PK/PD models is rare, but these could feasibly be included in Bayesian prediction algorithms to predict and adjust dosing strategy on an individual level .…”
mentioning
confidence: 99%
“…We are getting closer to the point where, using dashboard systems, the pharmacokinetics and early drug clearance can be predicted and could be integrated in the T2T approach. 100 A strength of the evidence presented in this review is the availability-though very limited-of real-world data. It will be critical that T2T strategies are adequately tested in pragmatic studies, as adopting treatment algorithms in practice can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate a broader application, the American Gastroenterology Association published a paper with recommendations for reactive TDM (62). Although not all studies used the same bioanalytical method to measure drug concentrations, independent reviewers from the society have indicated that results from various assays appear to be generally in good agreement (62,63) although a retrospective study showed that some assays do not have good performance (54).…”
Section: Defining Desired Systemic Exposure (Range)mentioning
confidence: 99%
“…With a PK model, incorporated patient factors, and a Bayesian approach, the dashboard system utilizes the concentration data from the previous dose and calculates the exact dosage a patient should receive and the exact date this dosage should be given to maintain a certain drug concentration. To make this prediction as accurate as possible, frequent blood sampling throughout treatment is desirable, although not necessary (54,55). However, care should be taken to ensure that the underlying structural model in the dashboard is appropriate.…”
Section: Maintaining Effective Mab Exposure-introduction Of Therapeutmentioning
confidence: 99%